The Accessibility of American Catholic Secondary Schools to the Various Socioeconomic Classes of Catholic Families - Huber, CSB, John B. (Catholic Education: A Journal of Inquiry and Practice, 2007)
The purpose of this study was to discern which socioeconomic classes are represented in Catholic high school populations across the United States. In addition, the study sought to discover the motivations of those families whose children were currently enrolled in American Catholic high schools. Also explored were the reasons why Catholic families who have sent their child or children to Catholic elementary schools were electing not to continue Catholic education at the secondary level. Because financial aid availability has risen along with tuition (Tracy, 2001), this investigation included the extent to which such financial aid was considered by Catholic families, as well as the perceptions of Catholic families as to its availability at the secondary level. As tuition rates rise at a higher level than the cost of living and averages wage increases, this study additionally examined the extent to which the assertion (Baker & Riordan, 1998, 1999; Riordan, 2000) that American Catholic high schools were becoming more elitist is true. The Catholic Church’s statements as to the accessibility of Catholic education to all social classes provided a framework throughout the investigation.